Customer Relationship Management Strategy in Mobile-Based E-Commerce Platform Development to Increase Purchase Interest - Br Purba, Yunita Dana; Haraha, Aninda Muliani (Information Technology and Science (ITScience), 2024)
The demands of technological developments trigger every company to be able to increase competitive advantages in order to create a smooth business process. Customer satisfaction in comparing expectations before making a transaction with the service directly felt by a customer is one of the elements that affect how succesful. Therefore, this study develops and implements a mobile-based e-commerce system equipped with a customer relationship management feature that aims to increase the involvement of interest and product purchases at the Tarigan Clothing Store so that it can provide very significant additional value in a product marketing process. This mobile-based e-commerce information system application also utilizes javascript technology as its interface design. The use of javascript is considered to facilitate access to the latest features in the e-commerce application that is built because of the high existence of javascript which continues to develop according to technological advances. This mobile-based e-commerce application is expected to provide wider reach, convenience and become a more effective marketing tool for customers and Tarigan Clothing Store so that it can provide significant benefits for both parties and create a more comfortable and efficient shopping process.